Vertical Electrical Soundings from the Lodwar Alluvial Aquifer System, Turkana County, Kenya - Tanui, F; Olago, D; Ouma, G; Kuria, Z (University of Oxford, 2024)
A total of 27 vertical electrical soundings (VES) were conducted within the Lodwar Alluvial Aquifer System (LAAS) to investigate subsurface geology and estimate the depth of aquifer units in February 2019. The Schlumberger configuration was employed, where current was passed through two electrodes (A and B) while measuring the potential difference between electrodes (M and N). The survey, conducted across Sections A-D of the LAAS, utilized PASI 16 GL-N model geophysical equipment to acquire data. Apparent resistivity values were determined by multiplying resistance products by the terametre and geometric factor, with current electrode spacing ranging from 1 to 200 meters and potential electrode spacing from 0.5 to 10 meters. Data interpretation involved plotting apparent resistivity against electrode spacing using IP2WIN inversion software, and results were visualized with log-log graphs showing resistivity profiles and depth to various geoelectric layers. Due to poor potential contact, VES 2 was excluded from the analysis, making the total valid VES results to be 26. The final geoelectric layer distribution was plotted using Golden Software Surfer Version 16. The results provide detailed insights into the vertical resistivity distribution, which is crucial for understanding the subsurface structure and depth of aquifer units within the LAAS, aiding in groundwater exploration within the LAAS.